THE INFLUENCE OF ROLE PLAY TECHNIQUE TOWARDS STUDENTS’ SPEAKING SKILL ON NARRATIVE TEXT AT NINTH GRADE OF SMP NEGERI 1 TEMBILAHAN HULU - Pratiwi, Bella Azelina; Ardian, Edi; Erma Purwanti, Sri (Program Studi Pendidikan Bahasa Inggris, 2022)
The purpose of this study was to determine the effect of role-play techniques on students' English-speaking skills using narrative texts. The research method used is the experimental method. In collecting data using a questionnaire and a test of the students' English-speaking ability, The subjects of this study were grade IX students of SMPN 1 Tembilahan Hulu. The results of the analysis show that the results of the analysis show that the t-observed is higher than the t-table (14.24 > 2.75 or 14.24 > 2.45) at a significant level of 5% or 1% with degrees of freedom (df) = 30 This means that the null hypothesis (H0) is rejected and the alternative hypothesis (H1) is accepted. This also means that the role-play technique affects the English-speaking skills of students who study narrative texts in class IX at SMP Negeri 1 Tembilahan Hulu.